Isochoric thermal conductivity of solid nitrogen - Konstantinov, V.A.; Manzhelii, V.G.; Revyakin, V.P.; Sagan, V.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2005)
The isochoric thermal conductivity of solid nitrogen has been investigated on four samples of different densities in the temperature interval from 20 K to the onset of melting. In a-N2 the isochoric thermal conductivity exhibits a dependence weaker than Λµ1/T; in b-N2 it increasesslightly with temperature. The experimental results are discussed within a model in which the heatis transported by low-frequency phonons or by «diffusive» modes above the mobility edge. The growth of the thermal conductivity in b-N2 is attributed to the decreasing «rotational» componentof the total thermal resistance, which occurs as the rotational correlations between the neighboring molecules become weaker.